Exploring the Impact of Trade and Investment on Income Inequality: A Cross-National Sectoral Analysis of the Developed Market Economy Countries - Vincent A. Mahler; David K. Jesuit; Douglas D. Roscoe (Luxembourg Income Study (LIS), 1997)
The central aim of this paper is to explore the relationship between international integration and domestic inequality in the developed market economy countries in the mid-1980s and early 1990s. The analysis examines two major modes of integration trade and direct foreign investment disaggregating each by economic sector and distinguishing between imports and exports, and inbound and outbound investment flows and stocks. The study finds few significant relationships between either trade or investment and any indicators of sectoral income distribution. The overall conclusion is that economic globalization is not a critically important factor explaining recent trends in income inequality in the Western world.
Keywords: 330; Regionale Einkommensverteilung; Internationale Wirtschaftsbeziehungen; Auslandsinvestition; Industrieländer